The Impact of Profitability and Earnings Management on Tax Aggressiveness with Corporate Governance as Moderating Variables (Study on Registered Energy Sector Companies on the Indonesia Stock Exchange in 2019-2021) - Jessica Tanujaya; Binsar H Simanjuntak (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study discusses the phenomenon of tax aggressiveness in energy sector companies in Indonesia. The research sample is companies listed on the Indonesia Stock Exchange in 2019-2021 which were selected using the purposive sampling method. Data processing uses panel data regression analysis with the help of Eviews 10 software. The results show that profitability and earnings management have a positive and significant effect on tax aggressiveness. Meanwhile, corporate governance cannot moderate the influence of independent variables on tax aggressiveness.